Pengembangan Modul Pembelajaran Konsep Genetika dengan Filosofi Mapalus dan Pendekatan Keterampilan Metakognitif - Yermia Semuel Mokosuli (Universitas Pendidikan Ganesha, 2024)
Learning in the era of the industrial revolution 4.0 requires students to learn how to integrate concepts at all levels of organization and complexity as well as synthesize and analyze information that connects conceptual domains. A metacognitive approach will instill the skills the current generation needs to interact in society and the world of work. The aim of the research is to describe students' responses to the genetics learning module with the Mapalus philosophy approach to metacognitive skills. This research applies development research methods. Media experts' responses to the module were valid (78%), while material experts' responses were very valid (85%). The genetic concept module developed using the Mapalus local wisdom approach produced good responses from students both in terms of use and cognitive assessment results. The module also raises students' soft skills in their use, namely cooperation, leadership, the ability to divide tasks in groups and present the results of group work. The module developed is also able to improve students' metacognitive abilities. Students' ability to understand problems increased from 65 to 80 (maximum score 100). The ability to perform calculations increased from 55 to 70. The ability to make problem solving plans increased from 67 to 75. The Genetic Concepts Module with the mapalus philosophy and metacognitive approach can be applied in schools.